Dermatology consultation service at a large metropolitan hospital system serving minority populations. (22nd June 2020) - Fayne, R.; Castillo, D.E.; Sanchez, N.; Burroway, B.; Nanda, S.; De Bedout, V.; Stratman, S.; Rosen, J.; Darwin, E.; Nagrani, N.; Gonzalez, A.; Paul, S.; et al.
Abstract: Background: Dermatology consultations in the inpatient hospital setting can improve diagnostic accuracy and management. Objective: Characterize dermatologic diagnostic and treatment trends in the hospital setting and identify variables that may affect patient care. Methods: Retrospective chart review from 1 January 2012 to 31 December 2017 at Jackson Memorial Hospital (JMH) (Miami, Florida, USA), an academic non‐profit tertiary care centre affiliated with University of Miami Miller School of Medicine, was performed. Patients who received dermatology consultations in the emergency department (ED) or inpatient settings were included. Patient demographics, admission information, provisional diagnosis and management plans by primary teams, final diagnosis, management plans and testing recommendations by the dermatology consults team, and follow‐up information were collected. Analysis using Microsoft Excel of how time to consultation, admission length, inpatient versus ED setting and primary team affected diagnostic accuracy was also performed. Results: The 1004 consultations for 812 patients ( n = 812) were reviewed (359 women, 453 men). Most patients were Hispanic ( n = 359; 44.2%) or African American ( n = 273; 33.6%). Mean admission length was 20.6 days (range 0–439; median 6). The most common consulting service was internal medicine ( n = 452). In 387 cases (47.6%), primary teams did not give a provisional diagnosis. The most common provisional diagnoses were bacterial infection ( n = 93), viral infection ( n = 49) and drug reaction ( n = 44). The most common diagnoses by dermatology were viral infection ( n = 93), bacterial infection ( n = 90) and drug reaction ( n = 80). Dermatology consultation changed the provisional diagnosis in 55.7% of cases, more often in cases where consultation took place ≥2 days after admission ( P < 0.05). Primary teams followed dermatology treatment recommendations in 85.2% of cases. Conclusion: Dermatology consultation improves diagnostic accuracy in skin disorders in the hospital setting and serves as a valuable resource for inpatient care. A notable aspect of data from this study is the unique patient population, predominantly comprised of underrepresented racial and ethnic minorities including Hispanics and African Americans.